The relationship between gender and attitudes toward marriage - Servaty, Lisa; Weber, Kirsten (My University, 2011)
Marriage as a social institution is vulnerable; fewer people in western societies are marrying, and divorce rates are increasing throughout the world (Beach & Fincham 2010). The purpose of this study was to examine if there is a relationship between gender and attitudes towards marriage. The central research question in this study was "Are there gender differences in a sample of college students regarding their attitudes and beliefs towards marriage?" It was hypothesized that females would have stronger attitudes than males in support of marriage and that people marry mostly for love. Male and female college-aged students were surveyed at a small Midwestern university on their attitudes towards marriage. Survey data was statistically analyzed using cross-tabulations, mean comparisons, independent t-tests, and a Cronbach's Alpha reliability analysis. Both males and females were in support of marriage, and thus, no gender differences were found, and the first hypothesis was not supported. There was partial support found for the second hypothesis; although both genders agreed that people marry mostly for love, females expressed stronger attitudes. Implications for practitioners would be to not minimize the importance of marriage for young people in spite of the trend towards cohabitation. Implications for future research include using a large, random, national sample in order to be able to generalize the findings.
Keywords: Marriage; College students--Attitudes